Development of Digital Teaching Materials for Local History Courses to Improve Learning Effectiveness and Support the MBKM Program: Pengembangan Bahan Ajar Digital Mata Kuliah Sejarah Lokal untuk Meningkatkan Efektivitas Pembelajaran dan Mendukung Program MBKM - ROMADLONI, SAHRU; Riztika Widyasari; Dian Arief Pradana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The development of digital local history teaching materials at Universitas Banyuwangi on 17 August 1945 is based on the need to digitise teaching material content, learning models, learning strategies and assessment instruments uploaded through e-learning and integrated into the Ministry of Education and Culture's SPADA. The local history learning process also often takes place conventionally so that it is not in accordance with the MBKM programme. The purpose of this research is to develop local history teaching materials in digital form to increase participation to improve learning effectiveness. The research method used uses the A.D.D.I.E. development model which includes five stages; Analyse, design, develop, implement, evaluate. Based on the results of statistical tests conducted using the SPSS programme, the average post-test score of the experimental class was 82 and the average post-test score of the control class was 74.2. While the t-test obtained a value of 6.621 with a significance level of 0.000 less than 0.025 (0.000 <0.025), so Ho is rejected or there is an average difference between the experimental class and the witness class. In conclusion, the developed local history digital teaching materials effectively improve learning effectiveness.